South African land reform strategy : a panacea for unlocking developmental debacles - Kgobe, F. K. L.; Makalela, K. I. (IPADA, 2019)
The purpose of this paper is efficaciously to evaluate if land reform remains a pertinent a strategy for unlocking development in South African socio-economic realm. Pragmatically access to land habitually perpetuate and lead to explicit advancement for unlocking development in spheres of socio-economic conditions. The latter is lamented by the disillusioning acts of confiscation of South African land without remuneration. The South African land reform remains a lip-serviced subject of contention, notwithstanding the unsurpassed strides undertaken by the contemporary government regime through its wider legs of restitution, tenure reform and redistribution. Moreover, the wider legs of reform were explicitly found to serve as rudimentary within which progress towards unlocking developmental debacles can be measured. The paper is purely theoretical, it's a desktop study which relied heavily on the literature review to underpinned the argument. The paper takes cognizance of section 25 of the Constitution of the Republic of South Africa, 1996 to extract and expatiate the argument. The paper argues that the demise to development planning and practices is inextricably linked to inability of the government to operationalize land reform strategy. The land dispossession during the colonial era and the decades of apartheid regime rule produced an enormous unequal pattern of land ownership that served as impediments to development and unrelentingly perpetuated widespread rural poverty in South African communities. Keywords: Land, Poverty, Perceptions, Government, Gradualism
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Land; Poverty; Perceptions; Government; Gradualism; Economic assistance, Domestic - Law and legislation -- South Africa; Land reform -- South Africa